Effect of carbon dioxide (CO2) suppression on explosive limits of methane - Mohd Hafizul, Md Jais (2010)
Theoretical models to predict the upper/lower explosive limits of a mixture composed of hydrocarbon and inert carbon dioxide(CO2)are proposed in this study.It is found theoretically that there are linear relations between the reciprocal of the upper/lower flammability limits and the reciprocal of the molar fraction of hydrocarbon in the hydrocarbon/inert gas mixture.These theoretical linear relations are examined by existing experimental results reported in the literature,which include the cases of methane.The experiments were performed in a 20 L closed explosion vessel.The mixtures were ignited by using spark permanent wire that placed at the centre of the vessel. Inthis study,the result shows the lower explosive limits (LEL)and upper explosive limits(UEL)is from 5 vol% to 20vol% of methane(CH4)and have revealed that the addition of suppression agent as 5 vol% and 10 vol% carbon dioxide (CO2) in methane extends the lower LEL and UEL initially 9 vol% to 18 vol% and 3 vol% to 16 vol%.